Residential child care in Scotland: themes for practice since Another Kind of Home - Angus Skinner (Scottish Journal of Residential Child Care)
In this very personal account, Angus Skinner, former Chief Social Work Adviser to Scottish Ministers, and author of Another Kind of Home (1992), a review of residential child care in Scotland, considers enduring themes for practice and leadership. Along with good communication, good education, and training for staff and managers, he concludes that state care needs to develop the capacities to love and be loved.